Evaluation of John B. Cobb, Jr.’s Ecological Model, With the Focus on Its Workability in the Context of Bangladesh - Sayem, Md. Abu (Studia Ecologiae et Bioethicae, 2023)
The “ecological model” of John B. Cobb, Jr. seems a timely and needed approach to address our present ecological crisis. Keeping Cobb’s “ecological model” of life and development in hand, the present paper attempts to examine why this model seems significant especially for Bangladeshi people and how it can be applied in Bangladesh to reduce the environmental issues. In terms of methodology, it follows the methods of literature review and interpretive analysis. The required data is collected by primarily reviewing Cobb’s eco-theological works and then is used in the paper after analysis. Similarly, it investigates the applicability of his proposed ecological model in the context of Bangladesh and critically analyses the model by comparing socio-religious, political, and economic perspectives of Bangladesh. The study evaluates to what extent Cobb’s suggestion may be implemented and to what degree it should be modified, proved to be inconsistent or rejected. As the project connects Cobb’s eco-theological understanding with the present environmental problems of Bangladesh, its prime result will be motivating Bangladeshi people from grassroots levels to maintain ecological equilibrium by diverting their attention from the mechanistical and materialistic view to an organic view of the environment. Alongside these, the study will enrich the current discussions on the role of religions in environmental sustainability from a Bangladeshi perspective.